(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The aim of this paper is to provide a chronological overview of the most prominent women writers in Turkish literature starting from the 15th century till nowadays, with a particular review of characteristics of each period of the development which Turkish literature has gone through from the time of classical divan literature in the Ottoman Empire to the contemporary Turkish literature.